2022
DOI: 10.3389/fped.2022.867540
|View full text |Cite
|
Sign up to set email alerts
|

Updating Clinical Practices to Promote and Protect Human Milk and Breastfeeding in a COVID-19 Era

Abstract: The COVID-19 pandemic has impacted breastfeeding and lactation globally, with clinical practices implemented early in the pandemic being mostly anti-breastfeeding, e.g., separation of mothers from their infants, and not evidence based. As the pandemic has progressed, evidence has emerged reconfirming the value of human milk and the importance of protecting and supporting breastfeeding, especially the initiation of lactation. However, it is clear that COVID-19 has changed the clinical care paradigm around breas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 73 publications
1
7
0
Order By: Relevance
“…Differences in available studies could be due to the difficulty of discriminating whether a more severe clinical course is the result of an induced delivery or caesarean section imposed by the severe clinical condition of the mother, associated to neonatal complications connected to preterm delivery, mode of delivery and critical maternal conditions at the time of delivery, rather than to a real direct effect of the virus on the infants' organism 39 , 45 . In fact, our data support that the balance between the potential risk of postnatal transmission of the virus by the mother is decisively outweighed by the well-known benefits of skin-to-skin contact, rooming-in practice and above all, breastfeeding 6 . In fact, since the first wave of the pandemic, several international institutions, including the WHO, have issued guidelines that did not recommend the precautionary separation of the infected mother from her child 46 , 47 .…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…Differences in available studies could be due to the difficulty of discriminating whether a more severe clinical course is the result of an induced delivery or caesarean section imposed by the severe clinical condition of the mother, associated to neonatal complications connected to preterm delivery, mode of delivery and critical maternal conditions at the time of delivery, rather than to a real direct effect of the virus on the infants' organism 39 , 45 . In fact, our data support that the balance between the potential risk of postnatal transmission of the virus by the mother is decisively outweighed by the well-known benefits of skin-to-skin contact, rooming-in practice and above all, breastfeeding 6 . In fact, since the first wave of the pandemic, several international institutions, including the WHO, have issued guidelines that did not recommend the precautionary separation of the infected mother from her child 46 , 47 .…”
Section: Discussionsupporting
confidence: 63%
“…As a result, increased reliance on breast milk substitutes occurred 4 , 5 . However, many authors have demonstrated the safety of breastfeeding even during maternal COVID-19 infection, and nowadays, these concerns and the choice of formulated milk seem unjustified 6 . Furthermore, breastfeeding provides the optimum nutrition for the neonate and protects the infant against infection, even in the case of SARS-CoV-2 6 , 7 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite these reassuring data, guidelines and local practices that emerged during the pandemic were largely contrary to the promotion and protection of breastfeeding, including the restriction of parental presence at the bedside, complete separation of mothers who were either confirmed or suspected as COVID-19 positive from their infants, discouragement or abandonment of skin-to-skin contact and direct breastfeeding, early discharge following birth, and a lack of access to in-person pediatric follow-up and breastfeeding assistance [21]. Therefore, especially in the first phase of the pandemic, separation of the newborns from their mothers was applied in many settings, even though such a practice has been considered a violation of human rights [22].…”
Section: Discussionmentioning
confidence: 99%
“…Apart from mortality and morbidity, the pandemic has also impacted all areas of health service delivery including breastfeeding. 4 At the start of the pandemic, the medical and scientific community lacked information regarding the route of transmission of the virus, thus many preventative measures were launched to protect mothers and babies. When it became evident that it is a respiratory virus, the next question was whether mothers could infect their infants during breastfeeding.…”
Section: Introductionmentioning
confidence: 99%